Peripheral biomarkers to assess risk, severity, and prognosis of immune checkpoint inhibitor-associated myocarditis: a retrospective clinical study - Guan, Zhengkun; Yao, Tiezhu; Liu, Guang; Liu, Jing; Guo, Ling; Li, Zhenli; Ma, Jingtao (Frontiers in Cardiovascular Medicine, 2024)
Background: Immune checkpoint inhibitor-related myocarditis (ICI myocarditis) is an infrequent but potentially fatal immune-related adverse event. This study aimed to identify valuable indicators for risk prediction and evaluation of disease severity and outcomes. Methods: A total of 79 patients with severe or mild ICI myocarditis and 158 controls without post-ICI immune-related adverse events were enrolled in this retrospective study. The clinical application value of a series of simple biomarkers were tested. Results: Higher levels of the systemic immune-inflammation index (SII), neutrophilto-eosinophil ratio (NER), aspartate transferase-to-albumin ratio (AAR), and lactic dehydrogenase-to-albumin ratio (LAR) at myocarditis onset were associated with severe disease conditions. In the receiver operating characteristic analysis, biomarkers areas under the curve (AUC) close to or greater than 0.8 were LAR (AUC: 0.810) and AAR (AUC: 0.806). Patients with higher SII, AAR, and LAR also exhibited poorer overall survival. The SII, NER, AAR, and LAR before the last ICI treatment increased relative to baseline in patients with ICI myocarditis, whereas no significant changes in the tested biomarkers were observed in the control group. For SII, AAR, and LAR, high ratios of the biomarker levels before the last ICI to baseline was associated with the incidence of myocarditis. Conclusions: Surveillance of these economical biomarkers during ICI therapy might contribute to the risk prediction of ICI myocarditis, as well as the assessment of disease severity and prognosis.